Age-related influence on physical fitness and individual on-duty task performance of Portuguese male non-elite police officers - Teixeira, João (2019)
(a) to analyse the effect of age on physical fitness (PF) and on-duty task (ODT) performance of male police officers (PO); (b) to analyse the relationship between PF and ODT performance of male PO; and (c) to identify the set of PF attributes which better predicts the ODT performance of male PO. A total of 97 Portuguese male non-elite PO (Public Security Police) took part in this cross-sectional study. Participants were allocated to four age categories (20-29, 30-39, 40-49, and >49 years old), and performed fourteen PF evaluations and one on-duty task simulation test (ODT-ST). MANOVA, partial correlations and multiple linear regression analysis were used. We observed (a) a significant decrease of performance with aging (PF attributes, partial eta-squared=0.763; total time on ODT-ST, partial eta-squared=0.498); (b) significant positive associations between body mass index and fat mass with total time on ODT-ST; (c) a significant negative association between standing broad jump (SBJ), sit-up, push-up, bench-press ratio and aerobic capacity with total time on ODT-ST; and (d) that SBJ, abdominal muscular endurance and aerobic capacity were significant predictors of total time on ODT-ST (R2=0.983). PF attributes and ODT performance of Portuguese male non-elite PO decrease significantly with aging. To prevent the observed decrease of performance it seems advisable to implement regular strength and conditioning programmes, which should include muscular power, core strength and aerobic fitness development, to maintain physical capacity and occupational duties.